The Church and the Spirit in Robert Jenson's Theology of Scripture. Issue 3 (August 2019) - East, Brad
In the last two decades of Robert Jenson's career, he turned his attention to the doctrine of Scripture and its theological interpretation. This article explores the dogmatic structure and reasoning that underlie Jenson's thought on this topic. After summarizing his theology of Scripture as the great drama of the Trinity in saving relation to creation, the article unpacks the doctrinal loci that materially inform Jenson's account of the Bible and its role in the church. Ecclesiology and pneumatology emerge as the dominant doctrines; these in turn raise questions regarding Jenson's treatment of the church's defectability: that is, whether and how, if at all, the church may fail in its teaching and thus in its reading of Scripture.